The Option-iPoD - Capuano, Christian (Washington, D.C. : International Monetary Fund, 2008)
We present a framework to derive the probability of default implied by the price of equity options. The framework does not require any strong statistical assumption, and provide results that are informative on the expected developments of balance sheet variables, such as assets, equity and leverage, and on the Greek letters (delta, gamma and vega). We show how to extend the framework by using information from the price of a zero-coupon bond and CDS-spreads. In the episode of the collapse of Bear Stearns, option-iPoD was able to early signal market sentiment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet